Application of Integrated Quality Management Transformational Studies in Higher Education - Alvi Razanah; Nanda Indah Putri; Masduki Asbari (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
With the implementation of integrated education quality management, the quality of national education education standards will be achieved. A quality management system that is implemented with a consistent commitment will provide benefits and success for all stakeholders in higher education institutions. So to achieve this benefit and success, it must be based on several established quality management principles. Starting the entry of foreign universities to enliven the "competition" that already exists in this country. Universities should not be seen as centers of science, research, and community service, but also as “knowledge-generating” enterprises that need to “compete” to ensure survival. Competition, as experienced by firms for profit, including competition in the areas of quality, price and service. Universities as non-profit entities also face the same thing. For the management of all that, knowledge and management skills are needed, namely the management of higher education.